Experimental Verification of a Dual Band CP Patch Antenna Using a Biased YIG Compound - Kampitaki, A.; Zervos, T.; Lazarakis, F.; Alexandridis, A.A.; Dangakis, K.; Fikioris, G.; Varouti, E.; Stamopoulos, D.; Vardaxoglou, J.C. (2013 LOUGHBOROUGH ANTENNAS AND PROPAGATION CONFERENCE (LAPC), 2013)
In this paper, we present a patch antenna design and fabrication that uses a ferrimagnetic compound, Yttrium Iron Garnet (YIG), as part of its substrate. It is proved via both numerical simulations and experimental measurements, that with suitable application of an external magnetic field, a reconfigurable behavior in terms of the polarization characteristics can be achieved. The antenna is reconfigured from a single band linear polarized to a dual band circular polarized one, with different polarization sense in each resonance band. Mixtures containing YIG and epoxy resin in various consistencies have been examined.